Studies on Nutritional Qualities of Ipomoea pes-tigridis Linn: A Fodder Plant from Kunwari Ravineland at Morena (M.P.), India - Sharma, D.P. (Asian Journal of Chemistry, 2010)
Ipomoea pes-tigridis Linn. is a spreading or twining herb, which appears during monsoon season in the ravineland of river Kunwari at Morena (M.P.), India. The plant is known as Ghiabati or Panchpatri by local people and is used as a feed of livestock in green state as well as hay. The plant is highly nutritive with peak of 4195.20.20 cal/g energy and 24.25% crude protein in October, 0.196% phosphorus content in September and 5.8% potassium in November.